Immunohistochemical analysis of hMLH1 and hMSH2 proteins in serous ovarian tumours - Stasikowska-Kanicka, Olga; Stawerski, Paweł; Wągrowska-Danilewicz, Małgorzata; Danilewicz, Marian (Polish Journal of Pathology, 2009)
Inactivation of DNA mismatch repair (MMR) genes is involved in carcinogenesis of sporadic and inherited human cancers. Mutations in MMR genes are associated with the loss of immunoexpression of hMLH1 and hMSH2 and may play a role in the mechanism of carcinogenesis of ovarian tumours. The aim of the study was to evaluate the immunoexpression of hMLH1 and hMSH2 in serous ovarian tumours. Sixty cases of benign, borderline, G1, G2 and G3 serous ovarian tumours were retrieved from the archival material. The immunoexpression of hMLH1 and hMSH2 was detected using an immunohistochemical method and a percentage of immunopositive cells in a 1000 tumour cells for each slide was measured. Loss of immunoexpression of hMLH1 and hMSH2 was infrequent in ovarian tumours, including both serous cystadenomas and carcinomas. Lack of immunoexpression of hMLH1 was observed only in 4 of 8 and hMSH2 in 5 of 8 of borderline cases. Moreover, the percentage of hMLH1 positive cells was significantly lower in borderline tumours as compared to G2 cancers. The percentage of hMSH2+ cells was in the borderline group significantly lower in comparison with all other groups investigated. Our results suggest that hMLH1 and hMSH2 proteins may be involved in ovarian carcinogenesis.